(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
Today, a comprehensive study of social aspects, cultural and spiritual, as well as socio-economic, legal, educational and organizational features of the women’s issue in our country is one of the most pressing issues. The relevance of the issue is that, first of all, at the present stage of development of our society, it is socially necessary to conduct a scientific analysis of the Islamic doctrine regarding the women’s issue in the process of increasing the spirituality of the Uzbek people, including religious literacy. Secondly, analyzing and studying the basic principles of Sharia norms, it is necessary to correctly use this knowledge to improve the role of women in the family and society, which is very important today. In this regard, this article highlights the essence and characteristics, as well as the socio-economic, spiritual and cultural foundations of women’s rights, in Islam, using the example of the verses of the Qur’an and Hadith, which were considered in the region as traditions. The article also examines the family rights and obligations of women, the status of women in society, the right to work, and social and economic rights regulated in Islam. It analyzes the spiritual, legal, educational factors of women’s rights set forth in regulatory acts adopted in the Republic of Uzbekistan.